Visualisation forms in passive sonar with towed array - Raganowicz, A.; Kilian, L.; Marszal, J.; Ostrowski, Z.; Schmidt, A. (Archives of Acoustics, 2006)
This paper presents forms of visualisation used in modern underwater systems, a topic covered at two previous Seminars. This year’s presentation describes how imaging is organised on the monitors of a passive sonar with a long acoustic array, towed behind the ship’s stern, part of a modernisation project at the Department of Marine Electronics Systems. The introduction gives an overview of the design of the sonar and the type of signals received and used for imagining. The article then describes the other factors, which are important for how images are organised, i.e. the operators’ tasks, the settings and how they are presented, other data from additional sonar sensors, how the systems works with the other on-board systems, operator training and ergonomics. Examples of images are included.